The influence of low-grade inflammation on platelets in patients with stable coronary artery disease - Larsen, Sanne Bøjet; Grove, Erik Lerkevang; Würtz, Morten; Neergaard-Petersen, Søs; Hvas, Anne-Mette; Kristensen, Steen Dalby (Thrombosis and Haemostasis, 2015)
Inflammation is likely to be involved in all stages of atherosclerosis. Numerous inflammatory biomarkers are currently being studied, and even subtle increases in inflammatory biomarkers have been associated with increased risk of cardiovascular events in patients with coronary artery disease (CAD). Low-grade inflammation may influence both platelet production and platelet activation potentially leading to enhanced platelet aggregation. Thrombopoietin is considered the primary regulator of platelet production, but it likely acts in conjunction with numerous cytokines, of which many have altered levels in CAD. Previous studies have shown that high-sensitive C-reactive protein (CRP) independently predicts increased platelet aggregation in stable CAD patients. Increased levels of CRP, fibrinogen, interleukin-6, stromal cell-derived factor-1, CXC motif ligand 16, macrophage migration inhibitory factor, RANTES, calprotectin, and copeptin have been associated with increased risk of cardiovascular events in CAD patients. Additionally, some of these inflammatory markers have been associated with enhanced platelet activation and aggregation. However, CRP and other inflammatory markers provide only limited additional predictive value to classical risk factors such as smoking, blood pressure, and cholesterol levels. Existing data do not clarify whether inflammation simply accompanies CAD and increased production and aggregation of platelets, or whether a causal relationship exists. In this review, we provide a comprehensive overview of inflammatory markers in stable CAD with particular emphasis on platelet production, activation, and aggregation in CAD patients.
Keywords: Inflammation; platelet aggregation; platelet production; antiplatelet therapy; coronary artery disease